Epifaunal and infaunal responses to submarine mine tailings in a Norwegian fjord - Trannum, Hilde C.; Borgersen, Gunhild; Oug, Eivind; Glette, Tormod; Brooks, Lucy; Ramirez-Llodra, Eva (Marine pollution bulletin, 2019)
Disposal of mine tailings in marine shallow water ecosystems represents an environmental challenge, and the present paper reports results from a field study in Frænfjorden, Norway, which is subject to such disposal. Structural and functional responses of benthic infauna and epifauna were investigated along a gradient from heavy tailings deposition to reference conditions. The tailings clearly impacted the faunal composition, with lowered species number close to the outfall. Total abundance of infauna increased in the most impacted area due to dominance of opportunistic species, whereas the epifauna was reduced and represented by a few scattered specimens only. In the most impacted area functional responses included an increase in mobile carnivores/omnivores and species utilizing symbionts. Sessile and tube-living taxa, and deposit and suspension feeders decreased, probably due to smothering in combination with tailings-associated changes of the substrate. Functional diversity decreased for both infauna and epifauna, but less than the structural diversity. [Display omitted] •Ecological effects on benthic fauna from submarine tailings disposal were studied.•Epifauna responded more strongly than the infauna.•Clear functional changes from heavily impacted to unimpacted areas.•Sessile tube-building species and deposit feeders were particularly affected.•Functional diversity decreased, but relatively less than the structural diversity.